Problems Experienced by Babies Between 4-36 Months During Teething Process and the Practices Made by Mothers - Zeynep Erkut; Selmin Köse; Fatma Dumandağ (Dokuz Eylul University, 2021)
Background: Teething is a physiological process that all babies experience. Many local and systemic symptoms are seen in this process. Objective: The study was carried out to determine the problems experienced by babies between 4-36 months during the teething process and the practices of mothers to cope with the problems. Methods: The descriptive and cross-sectional study was conducted between 30 October 2020-10 January 2021 in a Family Health Center in Istanbul. The sample of the study was the mothers of 145 babies registered in this center. The data were collected through the 'Questionnaire Form' prepared by the researchers as a result of the literature review. Data analysis was done in SPSS 22.0 program. Results: It was found that the mean eruption time of babies was 7.55 ± 2.24 (min = 4; max = 18) months. It was determined that the first tooth of the babies erupted was the right lower anterior incisor (49.0%), followed by the left lower anterior incisor (32.4%). It was found that most babies (95.9%) had at least one problem during teething and the most common problems were restlessness (76.6%), redness and itching of the gums (64.8%), increased bitting and chewing (55.2%), increased salivation (52.4%), sleeplessness (49.7%) and fever (48.3%). It was found that the most common practices of mothers for these problems were giving food to chew (71.0%), giving teething ring (60.0%), applying dental gel (43.4%), giving pain medication recommended by the physician (35.9%), and massaging the gums (34.5%). Conclusion: Almost all mothers stated that their babies have problems during the teething process. Parents should be informed about the selection of appropriate methods for these problems by the nurses.